The Economics of Political Transitions : Implications for the Arab Spring - Khandelwal, Padamja (IMF Working Papers; Working Paper ;, 2013)
Over the past two years, ongoing political transitions in many Arab countries have led to social unrest and an economic downturn. This paper examines comparable historical episodes of political instability to derive implications for the near- and medium-term economic outlook in the Arab countries in transition. In general, past episodes of political instability were characterized by a sharp deterioration in macroeconomic outcomes and a sluggish recovery over the medium term. Recent economic developments in the Arab countries in transition seem to be unfolding along similar lines, although the weak external environment and large fiscal vulnerabilities could result in a prolonged slump.